Quantum Nonlinear Optics with Polar J-Aggregates in Microcavities (2015)
We predict that an ensemble of organic dye molecules with permanent electric dipole moments embedded in a microcavity can lead to strong optical nonlinearities at the single-photon level The strong long-range electrostatic interaction between chromophores due to their introduces the desired nonlinearity of the light matter coupling the microcavity. We develop a semiclassical model to obtain the absorption spectra of a weak probe field under the influence of strong exciton-photon coupling with the cavity field. Using realistic parameters, we demonstrate that a cavity field with an average photon number near unity can significantly modify the absorptive and dispersive response of the medium to a weak probe field at a different frequency. Finally, we show that the system is in the regime of cavity-induced transparency with a broad transparency window for dye dimers. We illustrate our findings using pseudoisocyanine chloride (PIC) J aggregates in currently available optical microcavities.